Comprehensively Analyzed Macrophage-Regulated Genes Indicate That PSMA2 Promotes Colorectal Cancer Progression - Qi, Jingbo; Hu, Zhiqiu; Liu, Shaoqun; Li, Fan; Wang, Sheng; Wang, Wuqing; Sheng, Xia; Feng, Li (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is the thirdly common cancer worldwide. Here, we identified tumor associated macrophage (TAM) as a regulator gene in CRC. Totally, 457 genes expression were dysregulated after TAM co-culture, comprising 344increased genes and 113decreased genes. Bioinformatics analysis implied that these TAM-related genes had association with the regulation of the process of macromolecule metabolism, apoptosis, cell death, programmed cell death, and response to stress. For further uncovering the interplay amid these proteins, we established PPI networks and 15 key regulators were identified in CRC, containing VEGFA, FN1, JUN, CDH1, MAPK8, FOS. Amid the identified genes, we concentrated on PSMA2 and conducted loss-of-function experiments to validate the functions of PSMA2 in CRC. For further determining the mechanism of PSMA2 affecting CRC, we conducted multiple assays in CRC cell lines and tissues. PSMA2 enhanced cell proliferation, migration and invasion of CRC. What is more, our data indicated that PSMA2 was dramatically raised in stage 1, stage 2, stage3, and stage 4 CRC samples. Our data indicated that PSMA2 was one target of miR-132. MiR-132 mimic largely hindered cell proliferation of CRC. Besides, luciferase assay detection revealed that miR-132 directly regulated PSMA2. In addition, our data indicated that MiR-132 was largely reduced in CRC samples and was associated with longer survival time in CRC patients, implying that mir-132 was a probable biomarker for CRC. All data collectively indicated that PSMA2 was a promising target in the therapy of CRC.